Influência de polímeros bioadesivos sobre o efeito protetor do flúor no desenvolvimento da erosão dental - Ávila, Daniele Mara da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Dental erosion is a multifactorial process involving tooth demineralization by the chemical action of intrinsic and extrinsic acids. Since the protective effect of fluoride against erosion has been mainly related to fluoride adsorption and calcium fluoride deposits on tooth surface, it was hypothesized that the incorporation of bioadhesive polymers in fluoridated solutions would increase fluoride interaction with the enamel surface, and consequently, enhance its protective effect. In this study, three polymers were tested (Carbopol 980, Carboxymethyl Cellulose and Aristoflex AVC), in pretested concentrations based on the viscosity of the solutions to be used, which simulated a mouthrinse. Bovine enamel specimens were prepared and submitted to a demineralization-remineralization model with immersion in 0.3% citric acid, treatment with polymers solution associated or not to sodium fluoride (900 ppm), and storage in artificial saliva. Initial Knoop hardness (KHN1) and profilometry of all specimens were measured. After the first acid challenge, microhardness were measured again (KHN2), as well as after the first immersion in treatment solutions (KHN3) and after the second acid challenge (KHN4), characterizing the initial erosion analysis. Percentage of remineralization (%rem=KHN3-KHN2/KHN2*100) and of protection (%prot=(KHN4-KHN2/KHN2*100) was determined. The demineralization-remineralization cycling was repeated for five days, 6x/day, with immersion in treatment solutions after the first and last acid immersion of the day. At the end of the experiment, enamel loss was assessed with profilometry, by comparison of the initial and final profiles. Data were analyzed with ANOVA an Tukey's tests (p < 0.05). Regarding rehardening properties, no polymer isolated differed from control. When associated to NaF, Carbopol presented similar %rem compared to NaF control. For initial erosion protection,...

A erosão é um processo multifatorial que envolve a desmineralização dental pela ação química de ácidos extrínsecos ou intrínsecos. Visto que o efeito protetor do flúor contra erosão tem sido relacionado principalmente à formação de depósitos de fluoreto de cálcio e à adsorção de íons flúor na superfície dental, hipotetizou-se que a incorporação de agentes bioadesivos nas soluções fluoretadas poderia aumentar a interação de flúor aos tecidos e, consequentemente, potencializar seu efeito protetor. Neste estudo foram testados três polímeros (Carbopol 980, Carboximetil Celulose e Aristoflex AVC), em concentrações pré-determinadas com base na viscosidade da solução a ser utilizada, que simularam um enxaguatório bucal. Amostras de esmalte bovino foram confeccionadas e submetidas a um modelo de desmineralização e remineralização com imersão em ácido cítrico a 0,3%, pH 2,6, tratamentos com as soluções contendo os polímeros associados ou não ao fluoreto de sódio (900 ppm) e imersão em saliva artificial. Foram realizadas medidas de microdureza Knoop (KHN1) e análise perfilométrica inicial de todos os espécimes. Após o primeiro desafio ácido, foi realizada novamente leitura da microdureza dos espécimes (KHN2), bem como após a primeira imersão nas soluções de tratamento (KHN3) e o segundo desafio ácido (KHN4), caracterizando a avaliação da erosão inicial. A alteração de percentual de remineralização (% rem = (KHN3-KHN2/KHN2)*100) e de proteção (% prot = (KHN4-KHN2/KHN2)*100) foram determinadas. A ciclagem des-re foi repetida por cinco dias, 6x/dia, com imersão nas soluções de tratamento após a primeira e última imersão diária em ácido. Ao final do experimento, a análise perfilométrica final foi realizada para mensurar a perda de estrutura de esmalte, comparando-se a altura dos perfis inicial e final. Os dados foram analisados...
Keywords: Dentes - Erosão; Polímeros; Fluoreto de sódio; Esmalte dentário; Viscosidade; Dental enamel